2011
DOI: 10.1080/08997659.2011.620217
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Polymerase Chain Reaction (PCR) for Detection of Aquatic Animal Pathogens in a Diagnostic Laboratory Setting

Abstract: Real-time, or quantitative, polymerase chain reaction (qPCR) is quickly supplanting other molecular methods for detecting the nucleic acids of human and other animal pathogens owing to the speed and robustness of the technology. As the aquatic animal health community moves toward implementing national diagnostic testing schemes, it will need to evaluate how qPCR technology should be employed. This review outlines the basic principles of qPCR technology, considerations for assay development, standards and contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
59
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(60 citation statements)
references
References 71 publications
1
59
0
Order By: Relevance
“…Two of the protocols were not assessed for DNA copy numbers due to availability of information on the primer sequences for protocol 3 and for protocol 5 which was based on the Young et al (2008) primers which were used to produce the plasmid DNA. From the analysis of the three protocols assessed it was found that protocol 1 was able to detect the lowest concentration of copies of DNA at 2.64 copies µl −1 , which approaches the theoretical limit of detection (Purcell et al, 2011). Analysis of protocol 2 gave a concentration of 14.3 copies µl −1 which is similar to levels reported by Fringuelli et al (2012).…”
Section: Discussionsupporting
confidence: 65%
See 1 more Smart Citation
“…Two of the protocols were not assessed for DNA copy numbers due to availability of information on the primer sequences for protocol 3 and for protocol 5 which was based on the Young et al (2008) primers which were used to produce the plasmid DNA. From the analysis of the three protocols assessed it was found that protocol 1 was able to detect the lowest concentration of copies of DNA at 2.64 copies µl −1 , which approaches the theoretical limit of detection (Purcell et al, 2011). Analysis of protocol 2 gave a concentration of 14.3 copies µl −1 which is similar to levels reported by Fringuelli et al (2012).…”
Section: Discussionsupporting
confidence: 65%
“…Additionally, TaqMan R chemistry is generally thought to offer a number of advantages over SYBR R green, in particular, the incorporation of minorgroove-binders (MGB) which allow for the raising of melting temperatures of the probes (enabling the use of shorter probes) and integration of the internal hydrolysis probe providing greater specificity in comparison to the intercalating dye assays, which have reduced specificity because any amplification product incorporates the dye. (Gunson et al, 2006;Purcell et al, 2011). Each assay was designed to amplify specific regions of the 18S rRNA gene, which is generally chosen due to its high copy number, thus potentially increasing sensitivity.…”
Section: Discussionmentioning
confidence: 99%
“…The high virus copy number in samples may increase the likelihood of cross-contamination of samples during DNA extraction and assay preparation, and negative controls should be included throughout the sample processing. 19 It is advisable that samples representing different populations be processed separately to avoid cross-contamination. One approach commonly used to reduce potential false-positive test results is to select a quantification cycle cutoff value (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…However, such assays are difficult to implement due to the high degree of optimization that is required. Overall, qPCR assays are generally considered to have a large dynamic range, low interassay variation, and high reliability (Purcell et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Melioidosis endemic regions, especially rice-paddy communities and indigenous tribes, may not have access to these resources. However, competition has reduced initial start-up and operating costs of PCR/qPCR systems (Purcell et al, 2011). Although disadvantages of PCRbased methods exist, alternative detection methods have their own disadvantages in that they are usually slower and less accurate.…”
Section: Discussionmentioning
confidence: 99%